2019
DOI: 10.1177/1538192718823716
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mentoring on Hispanic Graduate Students’ Sense of Belonging and Academic Self-Efficacy

Abstract: This quantitative study examined the role of mentoring on 332 Hispanic graduate students' sense of belonging and academic self-efficacy. The results found that mentored Hispanic graduate students reported significantly higher levels of sense of belonging and academic self-efficacy than unmentored students. A hierarchical regression found 24% of the variance in academic self-efficacy was accounted for by mentoring and sense of belonging. Implications for practice and future research are discussed. Resumen Este … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…Parr et al ( 2020 ) identified belonging as the largest known correlate with symptoms of depression, accounting for nearly 50% of its variance. Other research has found benefits for mental health and emotional well-being (Allen et al, 2018b ; Arslan, 2018 ; Arslan & Allen, 2021 ; Arslan et al, 2020 ; Li & Jiang, 2018 ; Šeboková et al, 2018 ; Zhang et al, 2018 ), academic success, hardiness, social inclusion, and life satisfaction (Abdollahi et al, 2020 ; Arslan et al, 2020 ; Brooms, 2016 ; Palikara et al, 2021 ; Scorgie & Forlin, 2019 ), self-esteem and associated positive outcomes (Foster et al, 2017 ; Peng et al, 2019 ), lowered school dropouts (Organisation for Economic Co-operation and Development [OECD], 2018 ; Uslu & Gizir, 2017 ), reduced likelihood of absenteeism, misconduct, school disengagement or students leaving school early without a qualification (Ibrahim & El Zaatari, 2019 ; Korpershoek et al, 2020 ; OECD, 2018 ), decreased feelings of alienation, isolation and disaffection or low social integration and social exclusion (Arslan et al, 2020 ; Palikara et al, 2021 ), and better performance and self-belief in abilities to succeed academically (Chun et al, 2016 ; Holloway-Friesen, 2019 ). Recent research shows that a sense of school belonging is a significant predictor of future employment, education, and training (NEET) (Parker et al, 2021 ), even up to 15 years post-school, and our understanding of the role that school belonging plays in the psychosocial adjustment of students who have experienced traumatic events or other forms of stress (Cardeli et al, 2020 ; Zhang et al, 2021 ) has immense implications for educational practice, as well as therapeutic benefits.…”
mentioning
confidence: 99%
“…Parr et al ( 2020 ) identified belonging as the largest known correlate with symptoms of depression, accounting for nearly 50% of its variance. Other research has found benefits for mental health and emotional well-being (Allen et al, 2018b ; Arslan, 2018 ; Arslan & Allen, 2021 ; Arslan et al, 2020 ; Li & Jiang, 2018 ; Šeboková et al, 2018 ; Zhang et al, 2018 ), academic success, hardiness, social inclusion, and life satisfaction (Abdollahi et al, 2020 ; Arslan et al, 2020 ; Brooms, 2016 ; Palikara et al, 2021 ; Scorgie & Forlin, 2019 ), self-esteem and associated positive outcomes (Foster et al, 2017 ; Peng et al, 2019 ), lowered school dropouts (Organisation for Economic Co-operation and Development [OECD], 2018 ; Uslu & Gizir, 2017 ), reduced likelihood of absenteeism, misconduct, school disengagement or students leaving school early without a qualification (Ibrahim & El Zaatari, 2019 ; Korpershoek et al, 2020 ; OECD, 2018 ), decreased feelings of alienation, isolation and disaffection or low social integration and social exclusion (Arslan et al, 2020 ; Palikara et al, 2021 ), and better performance and self-belief in abilities to succeed academically (Chun et al, 2016 ; Holloway-Friesen, 2019 ). Recent research shows that a sense of school belonging is a significant predictor of future employment, education, and training (NEET) (Parker et al, 2021 ), even up to 15 years post-school, and our understanding of the role that school belonging plays in the psychosocial adjustment of students who have experienced traumatic events or other forms of stress (Cardeli et al, 2020 ; Zhang et al, 2021 ) has immense implications for educational practice, as well as therapeutic benefits.…”
mentioning
confidence: 99%
“…A mentor–mentee relationship framework can allow the creation of professional expectations and the establishment of a personal and collaborative relationship. Furthermore, mentoring can be an effective tool that can further impact overall achievement in terms of outcomes and increasing retention in graduate programs (Alcocer & Martinez, 2018 ; Holloway-Friesen, 2019 ; Klinge, 2015 ). In particular, mentorship by established BIPOC faculty can help students navigate academic culture, develop strategies for overcoming barriers related to race, and create road maps for desired career goals (Alegría et al, 2019 ; Cirincione-Ulezi, 2020 ; Fries-Britt et al, 2011 ).…”
Section: Increasing Diversity Among Behavior Analystsmentioning
confidence: 99%
“…The sense of belonging is defined as the perception of membership or feeling part of the educational organization (study program) in which they study [61]. Feeling belonging to the career implies that the student feels valuable and respected in their own educational program [40,[43][44][45][62][63][64][65][66]. It implies a perceived bond between the student and others, which unites them to a group or community, even in difficult moments or in the face of challenges [67], and the impulse that mobilizes them to create and maintain meaningful and lasting interpersonal relationships [68].…”
Section: Sence Of Belongingmentioning
confidence: 99%